Desenvolvimento e caracterização de ricota cremosa elaborada com soro de queijo coalho caprino e bovino - Borba, Karla Kaligia Silva (2013)
The ricotta cheese is a smooth flavor, obtained from the coagulation of the whey proteins in cheese with or without the addition of milk. May be fresh, creamy, aged or cured and can be consumed as cream cheese board or in combination with other ingredients in culinary dishes. The preparation of ricotta is an alternative to reusing whey, a co-product of high nutritional value generated in large quantities during processing of the cheese milk to obtain a curd type. In this study was to develop a base of creamy ricotta cheese curd goat whey (40%) and bovine (40%) as main ingredients, with added goat milk (10%) and bovine (10%). The technological characteristics, physicochemical and sensory texture of creamy ricotta were evaluated during refrigerated storage for 14 days. The yield of the process of getting the creamy ricotta was 7.9% and syneresis ranged from 5 to 7% during the study period. During storage, moisture (73.81 to 74.59), the lipid content (8.83 to 9.08) and total solids (25.63 to 26.19) remained stable (p >0,05), while the protein content and ash varied (p <0,05). The instrumental texture profile characterized the creamy ricotta cheese as an easily deformable, inelastic, cohesive, soft texture and delicate, unchanged after 14 days of storage. In the analyzes of instrumental color was observed reduction of yellowing and green tones during cold storage of 14 days. In Quantitative Descriptive Analysis (QDA) flavor and aroma of creamy ricotta goat were described by the panel as soft, wet appearance and soft texture and creamy. O fatty acid profile showed that the fatty acid content of medium and long chain (C14:0, C16:0, C18:0, C18:1n9c and C18:2n6c) was superior to just short chain acid (C6:0) and capric (C:10) decreased (p <0,05) during storage. Among the 14 identified amino acids, threonine, isoleucine, leucine and phenylalanine were increased during the study period, while methionine, lysine and alanine decreased. The results indicate that the use of the mixture of whey curd goat and bovine as the main ingredient of creamy ricotta mixed is viable and not reflected in negative features in the product, suggesting a promising use for reusing the coproduct.